2018
DOI: 10.31265/jcsw.v13i1.159
|View full text |Cite
|
Sign up to set email alerts
|

'He said he was going to kill me'

Abstract: This article uses a case study design to explore attempted intimate femicide in metropolitan São Paulo, Brazil. We conducted 30 in-depth interviews with adult women on community and personal relationship experiences, health-care services, and national legislation about violence against women. Through a thorough transcript review, we identified two participants, Maria* and Raquel*, whose intimate partners attempted to kill them. We used a modified grounded theory approach to code the entire sample, and further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Seven HBW are currently in operation including our study site in Curitiba, Brazil (Curitiba, 2016). Despite the promise of these structures, impunity for perpetrators of violence (Evans et al, 2018), lack of trust in the health and legal sectors (Evans et al, 2020a(Evans et al, , 2020b, barriers to addressing IPV among health providers (Evans et al, 2019), and other factors impede the prevention of IPV and femicide. A recent study revealed that the Curitiba's Metropolitan area faces higher rates of femicide compared to the state average and the most common location of these crimes was in the home (35%) using firearms (44%) (Wanzinack et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Seven HBW are currently in operation including our study site in Curitiba, Brazil (Curitiba, 2016). Despite the promise of these structures, impunity for perpetrators of violence (Evans et al, 2018), lack of trust in the health and legal sectors (Evans et al, 2020a(Evans et al, , 2020b, barriers to addressing IPV among health providers (Evans et al, 2019), and other factors impede the prevention of IPV and femicide. A recent study revealed that the Curitiba's Metropolitan area faces higher rates of femicide compared to the state average and the most common location of these crimes was in the home (35%) using firearms (44%) (Wanzinack et al, 2020).…”
Section: Introductionmentioning
confidence: 99%